The Effect of Work Motivation and Work Environment on Job Promotion - Ulum, Munawar Miftahul; Harsono, Yhonanda (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This research aims to analyze the effect of work motivation and work environment on job promotion at the Employee Cooperative of Bank Indonesia (KOPEBI), Jakarta. The study applies a quantitative approach with an associative method. The total population of 60 employees was used as the sample through a saturated sampling technique. Data were collected using a structured questionnaire and analyzed using SPSS version 26. The analysis includes validity and reliability tests, classical assumption tests, multiple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing. The results show that work motivation has a positive and significant effect on job promotion, with a t-value of 7.617 > 1.672 and a significance level of 0.000 < 0.05. The work environment also has a positive and significant effect on job promotion, with a t-value of 12.004 > 1.672 and a significance level of 0.000 < 0.05. Simultaneously, work motivation and work environment have a positive and significant effect on job promotion, indicated by an F-value of 71.266 > 2.766 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) is 0.711, meaning that 71.1% of the variation in job promotion is explained by both variables. These findings confirm that a motivated workforce supported by a conducive work environment contributes substantially to employees’ promotion opportunities at KOPEBI.